Crystallization of inorganic nonlinear optical zinc di-magnesium chloro sulphate (ZDMCS) single crystal. (February 2017) - Arivuselvi, R.; Ruban Kumar, A.
Abstract: The growth of inorganic zinc di-magnesium chloro sulphate (ZDMCS) nonlinear optical material from low temperature evaporation technique at ambient temperature has been reported. The dimension of harvested crystal is 28×10×2 mm 3 and is possess rectangular shape morphology. The single crystal X-ray diffraction studies confirmed that the grown crystal belongs to the system of trigonal. The S-Cl stretching vibrations and Mg 2+ ions present in the sample were observed by FTIR spectrometer. The cut-off wavelength of the grown crystal is about 203 nm is found by UV–visible absorption spectrum. The nonlinear optical efficiency was determined by powder Kurtz Perry technique. EDAX spectrum confirms the presence of elements within the material. Dielectric nature of the sample was analyzed for the frequency range 50 Hz to 5 MHz at different temperatures. The mechanical behaviour of the title compound was investigated using Vicker's microhardness tester. Graphical abstract: Highlights: Inorganic ZDMCS NLO material has been grown from aqueous solution by the slow evaporation technique. The cut-off wavelength of the crystal is found to be 203 nm. The EDAX spectrum confirms the Mg, O, Zn, Cl and S are present in the sample. Dielectric and mechanical behaviour of the material was also studied.